Potret Aceh antara Politik dan Hukum Syariat Islam (Analisis Novel Tanah Surga Merah karya Arafat Nur) - Bunga Fonna; Iswadi (Journal of English Education and Social Science, 2023)
This article is a research about An Analysis of the Novel Tanah Surga Merah by Arafat Nur. This research is intended to find out the portrait of Aceh between politic and Sharia law and to describe the impact of politic on the existence of Sharia law in Aceh. The whole process is carried out using the descriptive qualitative method, where primary and secondary data are collected to understand the whole research topic. The result of the analysis process shows that the local political system in Aceh has legitimized crime into the truth in the form of political and social hegemony. The hegemony causes Acehnese people to misapply the principles of life. Therefore, the presence of hegemony in Acehnese society had a very large negative impact on the survival of the social community. While the impact of politics on the existence of Sharia law in Aceh is the loss of moral values among Acehnese people that led them intentionally commit crimes even though they already know the truth. Key words: Politic, Sharia Law